BOOK DESIGN OF THE COMPANY KULTŪRA (1920–1937) IN ŠIAULIAI - KOŽENEVSKAJA, EMILIJA (Knygotyra, 2014)
The company Kultūra (1920–1937) in Šiauliai was one of the largest and most significant Lithuanian interwar commercial publishers. During the first decade of Lithuanian independence it foresaw the need to provide the public with editions, which were improved in both content and form. The publishing house tried to make its books similar to the publications released in Western Europe from the artistic point of view. The subject of the work is the Šiauliai company Kultūra book design from the artistic point of view. The aim is to determine design quality and characteristics of Kultūra books. The objectives are to explore the publishing activities of the company Kultūra; to analyze the company’s Kultūra attitude towards the design of the books; to identify the main factors influencing the aesthetic appearance of Kultūra books; to explore the stylistic features of the main artists who illustrated and designed the covers of the books of the company Kultūra; to analyze the design of the main types of the Kultūra company books with regard to their specifics. In the research, both general scientific and special bibliography methods were used. Analysis of primary the Kultūra company sources and scientific literature has led to the conclusion that considering difficult conditions of book production process and the lack of professional graphic artists in the third decade of the twentieth century, the company Kultūra was able to release quality books, meeting both the artistic and printing criteria of that time. Seventy percent of the company’s books were illustrated. The broad target audience demanded the development of both thematic and typological diversity ofthe publishing repertoire. Different artistic concepts of book types resulted in a diversity of illustrative material. The books printed in Germany have both a more attractive artistic design and a higher printing quality. The company Kultūra was able to choose a larger size of paper, to get clichés and replicas as well as to use offset printing. It pursued cooperation with the technically most powerful Lithuanian and foreign printing companies andinvited artists to design covers and illustrate books. All this is sufficient proof of how seriously the company Kultūra regarded artistic book design. The books were illustrated mostly by the popular artist Kazys Šimonis, eight coloured covers were designed by famous artist of Šiauliai Gerardas Bagdonavičius. A few books were illustrated by the Lithuanian artists Aldona Kazanavičienė, Antanas Kazanavičius and Pranas Giedravičius. Other books were illustrated by foreign artists Wilhelm Busch, Francz Müller-Münster, Paul-Gustave Doré and others.